Javanese Culture and Its Actualisation within Christian Faith: Study in the Gereja Kristen Jawi Wetan - Imaniyyah, Khalishah; Prameswari, Tasya Azheda Arni; Zahra, Tatu Azizatu; Adibah, Nisrina Fatin; Maulana, Abdullah Muslich Rizal (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2024)
In the East Java region, a Christian sect known as the Gereja Kristen Jawi Wetan exists. This particular sect incorporates Javanese cultural traditions into its worship rites. However, most religious communities believe they should not merge between culture and spiritual activities, as they consider them distinct and separate components. In this study, the researcher aims to accurately comprehend the significance of Javanese culture in executing worship rituals by the Gereja Kristen Jawi Wetan congregation. Integrating Javanese culture into these rituals is believed to enhance the congregation's faith. This study employs a qualitative-anthropological methodology to address the research inquiry by examining objects that have served as conduits to the supernatural, stemming from established societal practices. The researcher gathered data by employing interview procedures with multiple congregations and pastors and through direct observation. This interview ensured that the gained data aligned with the researcher's theory regarding the potential growth in faith resulting from the merger with Javanese culture. This study demonstrates the compatibility and integration of Christianity and Javanese culture without any discernible division. Conversely, the establishment of the Gereja Kristen Jawi Wetan provides a refuge for Javanese individuals who wish to maintain their cultural practices during religious ceremonies. This research inferred that the Gereja Kristen Jawi Wetan utilises Javanese culture to transmit religious values to the congregation. This strategy ensures that the adherents accept and absorb the teaching easily, enhancing the congregation's faith. Importantly, this spiritual practice recognises the cultural traditions deeply ingrained within the congregation.